J Mycobact Dis 2019
DOI: 10.35248/2161-1068.19.9.273
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Use of PCR as an Early Diagnostic Indicator of Bovine Tuberculosis in Dairy Farms

Abstract: Background: Zoonotic tuberculosis has been mainly associated with the consumption of bovine dairy products and its control has been prioritized by the Food and Agriculture Organisation. Objective: As such, the aim of this study is to assess whether the polymerase chain reaction (PCR) can be used as an early diagnostic indicator of Mycobacterium bovis infection in bovine dairy farms. Methods: Milk samples (n=78) were collected from all the animals older than 8 years of age, in all (n=4) bovine dairy farms locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Besides tissue samples, many PCR assays had been performed on blood and milk samples such as the Mataragka et al study, which illustrated that PCR can be used as an early and sensitive indicator method to detect infection in pooled milk samples collected from the aged animals of a dairy farm, which could support TST monitoring and improve bTB control [ 114 ]. In addition, Brahma et al reported a similar sensitivity of PCR targeting CFP-10 protein to that of IGRA and concluded that it may be used as a fast, alternative method for bTB diagnosis from blood samples [ 4 ].…”
Section: Diagnosis Of Btbmentioning
confidence: 99%
“…Besides tissue samples, many PCR assays had been performed on blood and milk samples such as the Mataragka et al study, which illustrated that PCR can be used as an early and sensitive indicator method to detect infection in pooled milk samples collected from the aged animals of a dairy farm, which could support TST monitoring and improve bTB control [ 114 ]. In addition, Brahma et al reported a similar sensitivity of PCR targeting CFP-10 protein to that of IGRA and concluded that it may be used as a fast, alternative method for bTB diagnosis from blood samples [ 4 ].…”
Section: Diagnosis Of Btbmentioning
confidence: 99%